Teachers’ Management of Everyday-Living Skills of Intellectually Challenged Learners - Adesegun Olayide Odutayo; Abdullateef Adeshina Adebayo; Habeeb Omoponle Adewuyi (Indonesian Journal of Early Childhood Education Studies, 2024)
Intellectually Challenged Learners (ICLs) are a long-lasting medical condition that affects people for the rest of their lives and typically prevents them from reaching their full potential. This study, therefore, investigated teachers’ management of Everyday-Living Skills (ELS) of ICLs. The research is survey-based and primarily descriptive. The study's population comprised instructors in public inclusive primary schools in Lagos State, Nigeria. The study’s sample consisted of 100 inclusive primary school instructors in total. The researchers employed a well-structured study questionnaire they had created to gather information on the “Management of ELS of ICLs.” A reliability index of 0.72 was calculated with the aid of the Spearman-Brown Prophecy Formula. A mean rating was used to address the questions posed. The t-test and Analysis of Variance (ANOVA) were used to evaluate the hypotheses at the 0.05 significance level. This study discovered that when teaching ELS to ICLs, the teacher-direct approach (TDA), generalization and application, task analysis (TA), and positive reinforcement and encouragement (PIE) were consistently used. The government should allot enough funds to equip instructors with the required instructional resources, assistive technology, and improved environments for effective ELS instruction.